Taiwan’s Financial Markets and Institutions: The Legal and Financial Issues of Deregulation and Internalization - Bennett, Michael S. (Columbia Journal of Asian Law, 1994)
Taiwan, the Republic of China (“Taiwan”) is one of the foremost economic success stories of the past thirty years. Numerous statistics attest to Taiwan’s remarkable economic development. As a newly industrialized country, its gross national product (GNP) is now roughly the twentieth largest in the world. Its per capita income has grown from only US196 in 1952 to over US8,000 today. Its foreign exchange reserves, valued at over US90 billion and rising, are the largest in the world. In short, Taiwan has emerged as one of the powerhouse economies of the Pacific Rim. Following a trail first blazed in Asia by Japan, Taiwan’s economic growth was based primarily on export-oriented manufacturing. Over the past thirty years, products manufactured in Taiwan, ranging from T- shirts to electronics, have carved out a significant share of global markets. The development of Taiwan’s financial system, however, did not keep pace with the island’s industrial development. Until quite recently, Taiwan’s financial markets were over-regulated and virtually closed to foreign participation.